Forensic Analysis on False Data Injection Attack on IoT Environment - Nizam S.A.S.; Ibrahim Z.-A.; Rahim F.A.; Fadzil H.S.; Mohd Abdullah H.I.; Mustaffa M.Z. (Science and Information Organization, 2023)
Advanced metering infrastructures; Digital forensics; Electric power system security; Electric power transmission networks; Network security; Water supply; Water supply systems; Cyber attackers; Electric power grids; Evidence collection; False data injection attacks; Forensic analysis; Forensic investigation; Internet of thing (IOT); Metering systems; Internet of things